Cash Is Alive: How Economists Explain Holding and Use of Cash - Shy, Oz (Journal of Economic Literature, 2023)
Research on holding and use of cash involves many aspects, such as reasons for holding and hoarding cash, transactional demand for cash, cash management, type of spending paid with cash, type of consumer who pays cash, merchant acceptance, how consumers get cash, currency denominations, legal aspects, cash substitutes, and cost of cash. The purpose of this article is to introduce the reader to some of the research economists do on consumer holding and use of cash. (JEL D11, D12, E26, E31, E41, E42)